Synthesis of higher alcohols during alcoholic fermentation of rye mashes - Pietruszka, Marta; Pielech-Przybylska, Katarzyna; Szopa, Józef (Wydawnictwo Politechniki Łódzkiej, 2010)
Formation of by-products during alcoholic fermentation is a complex process. Particular attention should be paid to generation of higher alcohols because of its complex mechanism and dynamics. In XIX century the higher alcohols were thought about as "bacterial metabolites of spoilage" that contaminate alcoholic beverages. At the beginning of XX century Ehrlich proved that these compounds were produced by yeast from amino acids and they naturally occurred in all alcoholic beverages derived from spirits of agricultural origin. The quantity and profile of fusel alcohols in the wash depend on many factors such as raw materials used to prepare the sweet mash, yeast strain and the inoculum dose, supplements added to the mash. Investigations of many researchers prove that higher alcohols are formed through catabolic and anabolic pathways. They are either products of amino acid catabolism -as was found by Ehrlich or by-products of amino acid synthesis from pyruvate through the anabolic pathway. The occurrence of fusel alcohols in raw spirits from agricultural distilleries is a result of the presence of amino acids, sugars and products of their metabolism mainly aldehydes, in fermented mashes.

Powstawanie poszczególnych produktów ubocznych podczas fermentacji alkoholowej, to proces bardzo złożony. Na szczególną uwagę, ze względu na mechanizm i dynamikę powstawania, zasługują wyższe alkohole. W XIX wieku, dominująca była opinia, że alkohole wyższe to "bakteryjne metabolity zepsucia", którymi skażone były napoje alkoholowe. Na początku XX wieku znane już były prace Ehrlicha, który wykazał, że wyższe alkohole są syntetyzowane przez drożdże z aminokwasów, a zatem są składnikami występującymi naturalnie we wszystkich napojach alkoholowych wyprodukowanych z alkoholu etylowego pochodzenia rolniczego. Na ilość fuzli w zacierze odfermentowanym, jak również na ich skład jakościowy, ma wpływ wiele czynników m.in.: rodzaj surowca użytego do przygotowania zacieru, rodzaj i wielkość inokulum drożdży oraz rodzaj pożywek, a także sposób prowadzenia fermentacji. Prace analityczne różnych autorów dowiodły, że wyższe alkohole mogą powstawać na drodze szlaku katabolicznego i anabolicznego. Szlak kataboliczny dotyczy przemian aminokwasów- w/w teoria Ehrlicha. Prekursorem w szlaku anabolicznym jest pirogronian, a fuzle są produktami pobocznymi, powstającymi podczas syntezy aminokwasów. Można jednoznacznie wnioskować, że występowanie fuzli w destylatach rolniczych jest efektem obecności w środowisku fermentacyjnym aminokwasów, cukrów oraz produktów ich przemiany, głównie aldehydów.
Synteza wyższych alkoholi w zacierach żytnich
Keywords: fermentacja alkoholowa; napoje alkoholowe; fuzle; synteza aminokwasów; teoria Ehrlicha